Summary for policymakers of the assessment report of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services on pollinators, pollination and food production - Potts, Simon G. (2016)
Fil: Potts, Simon G. Reading University. School of Agriculture, Policy and Development. Centre for Agri-Environmental Research; Reino Unido.